Finding the best combination of autochthonous microorganisms with the most effective biosorption ability for heavy metals removal from wastewater - Jakovljević, Violeta; Grujić, Sandra; Simić, Zoran; Ostojić, Aleksandar; Radojević, Ivana (Frontiers in Microbiology, 2022)
The presence of heavy metals (HMs) in the environment represents a serious environmental problem. In this regard, this work was conceived with the aim of finding, among indigenous microorganisms, the species and their combinations with the best biosorption activity for the following HMs: zinc, lead, cadmium, copper, and nickel. The experiment was carried out in several steps: 1) isolation and identification of microbial strains from the Central Effluent Treatment Plant's wastewater; 2) studying the interaction of microorganisms and the ability to form biofilms in 96 well plates; 3) testing the resistance of biofilms to HMs; 4) testing the growth of biofilms on AMB media carriers in the presence of HMS; and 5) biosorption assay. The selected strains used in this study were: Enterobacter cloacae, Klebsiella oxytoca, Serratia odorifera, and Saccharomyces cerevisiae. The best biofilm producers in control medium were K. oxytoca/S. odorifera (KS), followed by K. oxytoca/S. odorifera/ S. cerevisiae (KSC), and E. cloacae/K. oxytoca/S. odorifera (EKS) after 10 days of incubation. Mixed cultures composed of three species showed the highest resistance to the presence of all tested metals. The best biosorption capacity was shown by KSC for Cu2+ (99.18%), followed by EKS for Pb2+ (99.14%) and Cd2+ (99.03%), K. oxytoca for Ni2+ (98.47%), and E. cloacae for Zn2+ (98.06%). This research offers a novel approach to using mixed-biofilms for heavy metal removal processes as well as its potential application in the bioremediation of wastewater.